Factors Related to the Incident of Premature Rupture of Membrane among Maternity Women - Nazwita Dewi Putri; Shinta Novelia; Yenni Rahmawati (KHD Production, 2024)
In the health sector related to maternal and infant mortality, one of the causes is infection which many mothers experience, most of which are the result of pregnancy complications/complications such as fever, chorioamnionitis, urinary tract infections and 65% are due to premature rupture of membranes (PROM). which causes many infections in mothers and babies. At Salak Bogor Hospital, all cases of premature rupture of membranes in 2016 were 240 cases. This research is to determine the factors associated with the incidence of premature rupture of membranes in women giving birth at Salak Bogor Hospital in 2016. This research is an analytical descriptive study with a case control study approach. The total sample in this study was 300 people divided into a 1:1 ratio, which consisted of 150 respondents in the case group and 150 respondents in the control group, using simple random sampling techniques. Data collection was carried out using secondary data taken in the maternity ward at Salak Bogor Hospital in 2016. Data analysis used the chi square test with the SPSS version 24.0 program. The results of a study of 300 samples showed that the largest group of respondents in multigravida parity was 161 (53.7%), pregnancies without twins were 280 (93.3%), pregnancies without PROM were 295 (98.3%), mothers gave birth with normal position were 247 (82 .3%). The results of analysis using the chi-square test showed that twin pregnancies (p>0.247) and PROM (>1.000) were not proven to be related with PROM. Parity (p<0.005) and fetal position (p<0.001) were found related to PROM. It is hoped that the results of this research can be used as a source of information to increase mothers' knowledge about the factors associated with the incidence of premature rupture of membranes.